2021
DOI: 10.1126/sciadv.abb8087
|View full text |Cite
|
Sign up to set email alerts
|

IFNAR1 signaling in NK cells promotes persistent virus infection

Abstract: Inhibition of type 1 interferon (IFN-I) signaling promotes the control of persistent virus infection, but the underlying mechanisms remain poorly understood. Here, we report that genetic ablation of Ifnar1 specifically in natural killer (NK) cells led to elevated numbers of T follicular helper cells, germinal center B cells, and plasma cells and improved antiviral T cell function, resulting in hastened virus clearance that was comparable to IFNAR1 neutralizing antibody treatment. Antigen-specific B cells and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…In addition to regulating survival and functions of virus-specific CD4 T cells, IL-27 has been shown to play an important role in supporting Tfh functions during ovalbumin priming ( 28 ). Recent findings also indicated that Tfh cells are essential for the generation of LCMV-specific antibodies that drive clearance of persistent LCMV infection ( 7 , 16 ). Therefore, we investigated the impact of B cell–derived IL-27 on the numbers and function of Tfh cells during the chronic phase of LCMV infection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to regulating survival and functions of virus-specific CD4 T cells, IL-27 has been shown to play an important role in supporting Tfh functions during ovalbumin priming ( 28 ). Recent findings also indicated that Tfh cells are essential for the generation of LCMV-specific antibodies that drive clearance of persistent LCMV infection ( 7 , 16 ). Therefore, we investigated the impact of B cell–derived IL-27 on the numbers and function of Tfh cells during the chronic phase of LCMV infection.…”
Section: Resultsmentioning
confidence: 99%
“…Our group recently showed that blockade of IFN-I signaling led to increased numbers of Tfh cells in both WT and IL-27ra KO mice during persistent LCMV infection ( 6 8 , 31 ), and thus we further tested whether anti-IFNAR1 immunotherapy is able to improve functions of CD4 T cells and promote viral clearance. We first assessed Tfh numbers and function following anti-IFNAR1 antibody treatment at day 40 p.i.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, transient blockade of IFN-I early during LCMV infection can enhance antiviral T-and B-cell responses (30). Ablation of the IFNAR on NK cells exerts a similar effect (31). In MCMV and SIV/HIV infections, where NK cells exhibit potent antiviral function, this migration of NK cells to T-cell zones serves to protect these tissues from virus (15,19).…”
Section: Cxcr3 Is Required For Nk-cell Suppression Of Anti-viral T Cells Transient Localization Of Nk Cellsmentioning
confidence: 99%